CORRELATION OF NON-HIGH-DENSITY LIPOPROTEIN CHOLESTEROL WITH LIPOPROTEIN(A) IN DIABETIC PATIENTS - M, Vasanthan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to estimate the level of lipoprotein(a) and lipid profile, especially non-high-density lipoprotein cholesterol (non-HDL-C) in diabetic patients, and to correlate the same with healthy controls (non-diabetics). Methods: A total of 30 non-diabetic subjects and 30 diabetic patients were included in the study. Lipoprotein(a) (Lp[a]) was estimated by immunoturbidimetry and the other parameters by their respective methods in biochemistry auto-analyzer. Result: From the study, it was found that both Lp(a) and non-HDLC were increased in diabetics when compared to the non-diabetic controls. It was also evident that there is a positive correlation of Lp(a) levels with non-HDL C. Conclusion: Lp(a) and non-HDL C are responsible for atherogenic events in uncontrolled diabetic patients, leading to risks such as coronary artery disease.